Promoting Export: Some Lessons from Indonesian Manufacturing - Dionisius A. Narjoko; Raymond Atje (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
This study attempts to fill this gap and aims to draw some lessons from Indonesia's experience, by examining the export-supply response of firms in Indonesian manufacturing. The study asks two questions. First, what is the picture of export-supply response of firms in Indonesian manufacturing during and after the 1997/98 economic crisis?, and second, which factors determine the firms' export-supply response?
Keywords: F1; 330; Export; Indonesia; Indonesian Manufacturing